The sound of letting go - Kehoe, Stasia Ward. (New York : Viking, an imprint of Penguin Group (USA), 2014)
At seventeen, Daisy feels imprisoned by her brother Steven's autism and its effects and her only escape is through her trumpet into the world of jazz, but when her parents decide to send Steven to an institution she is not ready to let him go.
Keywords: Novels in verse; Autism -- Fiction; Trumpet -- Fiction; Jazz -- Fiction; High schools -- Fiction; Schools -- Fiction; Family problems -- Fiction; Autism -- Juvenile fiction; Trumpet -- Juvenile fiction; Jazz -- Juvenile fiction; High schools -- Juvenile fiction; Schools -- Juvenile fiction; Family problems -- Juvenile fiction